THE ROLE OF SOCIAL MEDIA IN GENERATION Z COMMUNICATION - Naomi Rebecca Siagian; Nina Yuliana (Ravine Publisher, 2024)
Social media has a significant role in human life, especially among young people such as Generation Z, who were born between 1996 and 2010. The use of social media greatly influences generation Z's daily activities. This journal explores the role of social media in generation Z communication dynamics through a qualitative research apprsoach. In an effort to understand how generation Z uses and interacts with social media, this research explores the complexity of experiences, views and identity construction formed through digital platforms. With a focus on interaction and interpretation, qualitative methodology was used to analyze data obtained from in-depth interviews, observations, and social media content analysis. The research results illustrate that social media is not only a communication tool but also an arena where generation Z builds and expresses their identity, values and communication patterns. These findings provide deep insight into how generation Z understands, responds to, and shapes their communication environment through social media use, highlighting the importance of social constructs in shaping their communication experiences.